Trust and Growth - Oguzhan Dincer; Eric Uslaner (Fondazione Eni Enrico Mattei (FEEM), 2007)
Using data from US states, we find a positive relationship between trust and growth. According to our results, a 10 percentage point increase in trust increases the growth rate of per capita income by 0.5 percentage point, growth rate of housing prices by 1.25 percentage points, and the growth rate of employment by 2.5 percentage points over a decade.
Keywords: Z13; R11; 330; Trust; Economic Growth; Vertrauen; Social Capital; Wirtschaftswachstum; Schätzung; USA